1979
DOI: 10.1136/bjo.63.3.165
|View full text |Cite
|
Sign up to set email alerts
|

Primary cutaneous malignant melanoma metastatic to the iris.

Abstract: SUMMARY We describe a case of cutaneous malignant melanoma metastatic to the iris as the first presenting sign of metastases 10 years after excision of the primary tumour. The histology of the excised iris metastases and the primary skin melanoma are compared. Progressive intracranial metastatic growth did not correlate with the observed regression of the residual intraocular melanoma cells during cyclical cytotoxic therapy.Iris metastases from primary cutaneous malignant melanomas are rare, with only 4 pathol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0
1

Year Published

1980
1980
2003
2003

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 17 publications
1
9
0
1
Order By: Relevance
“…The area where a cluster of melanoma cells was deeply seated in the iris stroma could well be the primary site of the iris metastasis. Histology of a small circumscribed melanoma metastasis in the iris has been reported [18]. Spreading tumour had also covered chamber angle, posterior iris surface, lens capsule, ciliary processes, zonular fibres, and vitreous, as has also been found by Font et al [2].…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…The area where a cluster of melanoma cells was deeply seated in the iris stroma could well be the primary site of the iris metastasis. Histology of a small circumscribed melanoma metastasis in the iris has been reported [18]. Spreading tumour had also covered chamber angle, posterior iris surface, lens capsule, ciliary processes, zonular fibres, and vitreous, as has also been found by Font et al [2].…”
Section: Discussionsupporting
confidence: 51%
“…Of the uvea the choroid is most frequently affected, location in the ciliary body is less common, metastasis to the iris, as in our first patient, is rather rare with only 13 eyes reported. Wagenmann [12], Adamiik [13] [4], and Hirst et al [18], each reported on one eye. De Bustros et al [19] reported on 2 unilateral and 1 bilateral case.…”
Section: Discussionmentioning
confidence: 99%
“…This report therefore emphasises the fact that the eye can be the initial site of a clinically identifiable recurrence of cutaneous malignant melanoma 6 , 8 and that ocular symptoms can develop up to 10 years after the excision of the primary tumour. 8 Treatment of cutaneous malignant melanoma metastatic to the viscera and eye is usually palliative, and consists of a combination of external beam radiotherapy and chemotherapy. Enucleation was required in this case as the tumour had become extensive, resulting in a blind painful eye.…”
mentioning
confidence: 99%
“…In the 3rd case no such predis position was found [2]: a malignant melano- ma of the lip with regional lymph node metastases was followed by a diffuse choroidal malignant melanoma 7 years later. In fact, first a new metastasis was suspected clinical ly, and indeed at least 34 such cases have been reported so far [8], Yet the histological examination demonstrated the ocular lesion to be a primary one. In our case the situation is different: the cutaneous lesion turns up about 6 years after the detection of the oc ular one and is diagnosed another 3 years lat er.…”
Section: Discussionmentioning
confidence: 99%